Rethinking Australia’s art history - Lowish, Susan, eauthor.
1 online resource (236 pages)
Keywords: This book aims to redefine Australia’s earliest art history by chronicling for the first time the birth of the category "Aboriginal art," tracing the term’s use through published literature in the late eighteenth, nineteenth and early twentieth centuries. Susan Lowish reveals how the idea of "Aboriginal art" developed in the European imagination, manifested in early literature, and became a distinct classification with its own criteria and form. Part of the larger story of Aboriginal/European engagement, this book provides a new vision for an Australian art history reconciled with its colonial origins and in recognition of what came before the contemporary phenomena of Aboriginal art.